2016
DOI: 10.5539/jas.v9n1p28
|View full text |Cite
|
Sign up to set email alerts
|

Urea Fertilizer Placement Impacts on Corn Growth and Nitrogen Utilization in a Poorly-Drained Claypan Soil

Abstract: Practices to increase nitrogen (N) use efficiency (NUE) include selecting appropriate N fertilizer sources and application methods, but minimal research has focused on these practices in poorly-drained claypan soils which are prone to N loss. This research assessed the impact of different urea fertilizer placement practices on corn (Zea mays L.) production and N utilization in a poorly-drained claypan soil. Field trials were conducted in 2014 and 2015 in Missouri. Treatments consisted of pre-plant deep banding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Surface treatments were no-tillage with surface applied nitrogen and deep treatments were strip tillage with deep banded nitrogen application. likely incorporated N from the fertilizer into the shallow soil layer and made N more available for plant uptake [17]. Similar to the results with an N rate of 84 kg•ha − 1 , corn grain yields were negatively affected by drought conditions in 2012 at 168 kg•N•ha − 1 ( Table 5).…”
Section: Corn Grain Yieldsupporting
confidence: 77%
See 1 more Smart Citation
“…Surface treatments were no-tillage with surface applied nitrogen and deep treatments were strip tillage with deep banded nitrogen application. likely incorporated N from the fertilizer into the shallow soil layer and made N more available for plant uptake [17]. Similar to the results with an N rate of 84 kg•ha − 1 , corn grain yields were negatively affected by drought conditions in 2012 at 168 kg•N•ha − 1 ( Table 5).…”
Section: Corn Grain Yieldsupporting
confidence: 77%
“…In addition to N application timing, fertilizer N placement strategies may improve crop yields and N use efficiency in claypan soils. Many studies have shown lower grain yields and N uptake with a surface broadcast N application compared to incorporated band N placement [6,[15][16][17]. Other studies did not observe any advantages of subsurface band placement of urea ammonium nitrate (UAN) over surface broadcast placement [8,18].…”
Section: Introductionmentioning
confidence: 99%
“…Early‐growing‐season flux of N 2 O observed in the DB+NI treatment suggested that NI lowered early soil NO 3 − concentrations or greater plant uptake occurred during the early and mid‐growing season, which decreased the concentration of NO 3 − substrate available for denitrification (Liu et al, 2017; Wolt, 2004). However, the late growing season peak in N 2 O flux in the DB+NI treatment could be explained by the short‐lived impact of NI or due to lower soil pH of the subsoil resulting in higher emissions of N 2 O (Johnson et al, 2016). Soil samples to a depth of 61 cm from all treatments were collected on 10 July 2017 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…All treatments increased N concentration in the silage compared to the NC; however, there was no statistical difference between DB, DB+NI, BCI, and BC treatments. Similarly, Johnson et al (2016) observed minimal differences in corn silage N concentrations between broadcast and deep‐banded N fertilizer.…”
Section: Resultsmentioning
confidence: 86%
“…Grain yield with DB or DB+NI was at least 8% greater than BCI in 2017. Johnson et al (2016) observed that deep‐banding urea resulted in 10% higher corn grain yields than broadcast and shallow placement of urea. Corn grain yield (11.29 Mg ha −1 ) was significantly lower with BC than BCI in 2016, but no differences were observed in 2017.…”
Section: Resultsmentioning
confidence: 99%